To study the effect of ceramic waste as fine aggregate to the properties of concrete - JATJO, KHAIRUL NIZAM; ABDULLAH, MOHD SUFYAN (Progress in Engineering Application and Technology, 2021)
This study was focus on partial replacement of ceramic waste as fine aggregate in production of concrete. This study is to identify whether the replacement of ceramic waste as fine aggregate can meet the requirement the standard of concrete for construction or have similar with natural fine aggregate. This research is study the properties of the ceramic waste in concrete mix and to identify the optimum percentage of ceramic waste as partial replacement of fine aggregate in concrete production based on the data from previous studies. The percentage replacement of ceramic waste are 10%, 20%, 30%, 40%, and 50%. Meanwhile, experiments that carried out on the specimen are slump test and compressive strength test at age 7 days and 28 days.